The End of Japanese Cinema : Industrial Genres, National Times, and Media Ecologies - Zahlten, Alexander, 1973- (Book collections on Project MUSE., 2017)
In The End of Japanese Cinema Alexander Zahlten traces the evolution of a new form of holistic media studies--media ecology--through historical overview and analysis of Japanese film and industry from the 1960s to the 2000s.